2020
DOI: 10.1371/journal.pone.0230127
|View full text |Cite
|
Sign up to set email alerts
|

Fatal overdose prevention and experience with naloxone: A cross-sectional study from a community-based cohort of people who inject drugs in Baltimore, Maryland

Abstract: Introduction Overdose is a leading cause of death in the United States, especially among people who inject drugs (PWID). Improving naloxone access and carrying among PWID may offset recent increases in overdose mortality associated with the influx of synthetic opioids in the drug market. This study characterized prevalence and correlates of several naloxone outcomes among PWID. Methods During 2018, a survey to assess experience with naloxone was administered to 915 participants in the AIDS Linked to the IntraV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 35 publications
3
14
1
Order By: Relevance
“…Those living with HIV who were unsuppressed at their last study visit were the most likely to report having naloxone on hand; however, this group may be the most stable due to their obvious engagement in care and adherence to ART. Reassuringly current PWID were most likely to report having a supply of both fentanyl strips and naloxone which reflects recent findings within our broader population ( Buresh et al, 2020 ). However, one-third of those actively injecting did not have a supply of naloxone on hand.…”
Section: Discussionsupporting
confidence: 74%
“…Those living with HIV who were unsuppressed at their last study visit were the most likely to report having naloxone on hand; however, this group may be the most stable due to their obvious engagement in care and adherence to ART. Reassuringly current PWID were most likely to report having a supply of both fentanyl strips and naloxone which reflects recent findings within our broader population ( Buresh et al, 2020 ). However, one-third of those actively injecting did not have a supply of naloxone on hand.…”
Section: Discussionsupporting
confidence: 74%
“…While we cannot say definitively that the scheduling change allowing for over-the-counter naloxone access was the impetus for increased awareness and/or use of naloxone this is an important area of inquiry for future research. Naloxone research in the United States with majority-male samples, for instance, has shown current opioid use, witnessing an overdose, and recent non-fatal experience of overdose were associated with greater naloxone knowledge and possession of a kit [ 83 , 84 ]. The opportunity for peer-led support in this study population needs to be highlighted, as women often learned about naloxone through informal social networks, instead of through health care providers.…”
Section: Discussionmentioning
confidence: 99%
“…If naloxone is needed for an overdose outside of the hospital setting, then in most cases emergency medical response systems should be activated for further support. [11][12][13][14]…”
Section: Overdose Reversalmentioning
confidence: 99%